Alnustone Ameliorates Metabolic Dysfunction‐Associated Steatotic Liver Disease by Facilitating Mitochondrial Fatty Acid β‐Oxidation via Targeting Calmodulin - Shourui Hu; Xiaofan Liang; Yiming Qin; Yuxuan Li; Yue Liu; Congcong Liu; Zongxuan Lin; Chunxuan Geng; Yanqi Xu; Daimin Wei; Yingying Qin; Han Zhao; et al. (Advanced Science)
Abstract Metabolic dysfunction‐associated steatotic liver disease (MASLD), including its more severe manifestation metabolic dysfunction‐associated steatohepatitis (MASH), poses global public health threats with limited therapeutics. Here, the role of alnustone is explored, a natural compound derived from the traditional Chinese herb Alpinia katsumadai Hayata, in the treatment of MASLD and MASH. It is shown that alnustone administration potently reduces serum triacylglycerol levels, reverses liver steatosis, and alleviates insulin resistance in both male and female MASLD mice. It also effectively ameliorates established fibrosis in MASH mice without any side effects. Mechanistically, hepatic lipidome profiling and energy metabolic assays reveal that alnustone facilitates mitochondrial fatty acid β‐oxidation. Employing limited proteolysis‐mass spectrometry (LiP‐SMap) and further validation, calmodulin is identified as a direct molecular target of alnustone. Alnustone interacts with the Ca2+‐binding site of calmodulin, leading to increased cytosolic and mitochondrial Ca2+ levels and enhanced mitochondrial function, whereas liver‐specific calmodulin knockdown abrogates alnustone's therapeutic effects. Moreover, calmodulin is downregulated in human livers of patients with MASLD and MASH, and is genetically associated with reduced MASLD risk. These findings establish alnustone as a promising natural compound and highlight calmodulin as a target for treating MASLD.